2009
DOI: 10.2147/plmi.s6249
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transcription factor zinc-binding protein-89 (ZBP-89) is inhibited by inflammatory cytokines

Abstract: Zinc-binding protein-89 (ZBP-89; ZNF148, BERF-1, BFCOL-1) is a zinc-finger transcription factor of the Kruppel family. It has been shown to regulate the expression of a number of genes, acting as either an activator or repressor of gene expression, depending on the context. It is over-expressed in several cancers, but has been shown to be involved in apoptosis and to have a negative influence on cell growth in part by interactions with p53. Previously, ZBP-89 was shown to activate transcription of the matrix m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…As a transcriptional factor, this gene is capable of influencing a lot on their tightly regulated genes. According to previous reports, ZNF148 mRNA and protein expression are significantly inhibited in human primary gingival fibroblasts by IL‐1β [16]. An exciting finding demonstrated that ZNF148 could bind to the MMP3 promoter at a polymorphic (5A/6A) site together with NF‐κB and further affect MMP3 protein levels.…”
Section: Discussionmentioning
confidence: 89%
“…As a transcriptional factor, this gene is capable of influencing a lot on their tightly regulated genes. According to previous reports, ZNF148 mRNA and protein expression are significantly inhibited in human primary gingival fibroblasts by IL‐1β [16]. An exciting finding demonstrated that ZNF148 could bind to the MMP3 promoter at a polymorphic (5A/6A) site together with NF‐κB and further affect MMP3 protein levels.…”
Section: Discussionmentioning
confidence: 89%